2019
DOI: 10.1021/acssuschemeng.9b01071
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Electro-Responsive Semi-Interpenetrating Starch/Ionic Liquid Copolymer Networks for the Controlled Sorption/Release of Biomolecules

Abstract: The main objective of this work was the development and characterization of sustainable electro-responsive ionic liquid-based cationic copolymers. For this purpose degradable semi-interpenetrating polymer networks (s-IPNs) based on starch and on ion-conducting cationic copolymers of 2-hydroxyethyl methacrylate (HEMA) and 1-butyl-3-vinylimidazolium chloride (BVImCl), cross-linked with N,N′-methylenebis­(acrylamide) (MBA), were synthesized by following principles of green chemistry. Cross-linked poly­(HEMA-co-BV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…However, it may be a risk when the usage of the starch-based FEs is large enough. The nondegradable components may be recycled by filtration or flotation Except for degradability, biocompatibility of the starchbased FEs was also concerned especially for medical applications, which can be confirmed through cytotoxicity tests 45,163 . The cell viability and the cell proliferation assays of the starch-based hydrogels were checked using Balb/3T3 fibroblasts cell in Kanaan's work (Fig.…”
Section: Degradability and Biocompatibility Of Starch-based Electronicsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it may be a risk when the usage of the starch-based FEs is large enough. The nondegradable components may be recycled by filtration or flotation Except for degradability, biocompatibility of the starchbased FEs was also concerned especially for medical applications, which can be confirmed through cytotoxicity tests 45,163 . The cell viability and the cell proliferation assays of the starch-based hydrogels were checked using Balb/3T3 fibroblasts cell in Kanaan's work (Fig.…”
Section: Degradability and Biocompatibility Of Starch-based Electronicsmentioning
confidence: 99%
“…Various sensors were fabricated on starch gels to obtain biocompatible devices 149,150 . Kanaan et al 45 synthesized a biodegradable semi-interpenetrating polymer networks (S-IPNs) based on starch and copolymer of 2-hydroxyethyl methacrylate (HEMA) and 1-butyl-3-metaprazor-lium chloride (BVImCl) cationic (Fig. 8b).…”
Section: Sensing Elements Based On Starch Gelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amylose is the linear part with α-1,4 linkages in the chain, has good extensibility in solution, and can readily bond by hydrogen bonding with polar chemical molecules. The amylopectin has a branched form and higher molecular weight with α-1,6 linkages in the branched parts and α-1,4 linkages at the backbone, , as well as the presence of plenty of −OH groups, which are beneficial for high proton conductivity in the presence of an external electrical field . Starch possesses the ability to gelatinize easily upon heating it in water at moderate temperatures (60–80 °C), where the hydrogen bonds between the starch molecules can be broken, dispersing in water to form a colloidal solution. , When the resultant solution becomes colder, the hydrogen bonds between the starch molecules are reformed and develop a three-dimensional network of a starch hydrogel via physical entanglement of amylose and/or amylopectin.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray scattering data indicated that the IPN adopted a lamellar structure while thermal analysis data supported the hypothesis that the resulting IPN was homogeneous. Since these initial findings, several other examples of IPNs and semi-IPNs have been reported, with a focus on tailoring the polymers toward specific applications such as gas separation, multi-responsive hydrogels, , and solid-state polymer electrolytes. The most conductive networks from this group were found to be on the order of 10 –4 S/cm at 25 °C.…”
Section: Introductionmentioning
confidence: 99%